1998
DOI: 10.1074/jbc.273.46.30660
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Activator 11 S Regulator or PA28

Abstract: The proteasome 11 S regulator (REG) consists of two homologous subunits, REG␣ and REG␤. Each subunit is capable of activating the proteasome, and when combined, they form superactive REG␣/REG␤ complexes. We have previously shown that a highly conserved loop in the REG␣ crystal structure is critical for proteasome activation. We now show that hetero-oligomers formed from REG␣ activation loop mutants and wild-type REG␤ or vice versa are partially active. By contrast, heterooligomers bearing mutations in the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…In any case, reconstitution of the ␣ and ␤ subunits restores full and efficient PA28 activity. This result has been explained alternatively by additive activities of each subunit or by modulatory effects of the ␤ subunit on the ␣ subunit (51,53). At least two domains of PA28 are important for its function.…”
Section: Pa28 An Atp-and Ubiquitin-independentmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, reconstitution of the ␣ and ␤ subunits restores full and efficient PA28 activity. This result has been explained alternatively by additive activities of each subunit or by modulatory effects of the ␤ subunit on the ␣ subunit (51,53). At least two domains of PA28 are important for its function.…”
Section: Pa28 An Atp-and Ubiquitin-independentmentioning
confidence: 99%
“…Recombinant PA28␤ is a monomer. Effects of isolated PA28␤ on proteasome activation have produced conflicting data, whose basis may relate to the very high concentrations of the subunit required to achieve proteasome activation (51,53). In any case, reconstitution of the ␣ and ␤ subunits restores full and efficient PA28 activity.…”
Section: Pa28 An Atp-and Ubiquitin-independentmentioning
confidence: 99%
See 1 more Smart Citation
“…The results (data not shown) indicated no detectable hybridization band from any of the DNA digests and thus suggested that a homologous PA26 gene is not present in the genome of any of the four other protozoan pathogens. Recombinant PA26 Can Self-assemble to Form a Heptamer Ring-Recombinant human PA28␣ was reported capable of self-assembly in vitro into a heptamer ring (22,23,37). Its crystal structure showed that the COOH terminus of each subunit protein is important for polymerization as well as interactions between the heptamer ring and mammalian 20 S proteasome, whereas the NH 2 terminus is apparently not involved (23).…”
Section: Determination Of the Partial Amino Acid Sequence Of Pa26 By mentioning
confidence: 99%
“…There are three isoforms of PA28: PA28␣, PA28␤, and PA28␥, sharing about 50% amino acid sequence identity (20). The ␣ and ␤ isoforms form a complex with 20 S proteasome in the form of a heptamer ring of three PA28␣ and four PA28␤ or three PA28␤ and four PA28␣ (21,22). The crystal structure of recombinant human PA28␣ has been recently resolved in the form of a self-assembled heptamer ring (23).…”
mentioning
confidence: 99%